Where is the intelligence in computational intelligence? - Pathan, Al-Sakib Khan (2005)
Intelligence is a controversial term to define in a universally acceptable way. However, the term is very frequently used in various fields of computer science like web intelligence, machine intelligence, artificial intelligence and overall in the computational intelligence. Some sort of intelligence has already been introduced to different advanced technologies. The future advancement of the intelligent technologies requires a clear definition of intelligence to work with. This paper tries to find out the answer of the crucial question, where and in which cases intelligence might exist in case of intelligent technologies and in the field of computational intelligence in general.